2021
DOI: 10.2147/jaa.s296391
|View full text |Cite
|
Sign up to set email alerts
|

Traditional Medicinal Plants Conferring Protection Against Ovalbumin-Induced Asthma in Experimental Animals: A Review

Abstract: Asthma is a chronic inflammatory disease of the respiratory tract in which the numerous immune cells, including eosinophils, neutrophils, macrophages, T-lymphocytes, mast cells and epithelial lining play key roles. The numerous anti-asthmatic drugs are available in modern medicine to treat asthma, but they have several disadvantages, including side effects and the cost variations, which compromise treatment compliance. The literature review reveals that traditional herbal medicines have good potential as alter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 117 publications
(187 reference statements)
0
19
0
Order By: Relevance
“…Asthma is a chronic inflammatory disease of the respiratory tract in which the numerous immune cells, including eosinophils, neutrophils, macrophages, T-lymphocytes, mast cells and epithelial lining play key roles. 14 Investigations of herbal-based interventions have shown that "herbs contain a large number of naturally occurring chemicals that have biological activity". Herbalists claim that the action of herbs is described according to the way it might affect human physiology.…”
Section: Discussionmentioning
confidence: 99%
“…Asthma is a chronic inflammatory disease of the respiratory tract in which the numerous immune cells, including eosinophils, neutrophils, macrophages, T-lymphocytes, mast cells and epithelial lining play key roles. 14 Investigations of herbal-based interventions have shown that "herbs contain a large number of naturally occurring chemicals that have biological activity". Herbalists claim that the action of herbs is described according to the way it might affect human physiology.…”
Section: Discussionmentioning
confidence: 99%
“…15 However, these drugs produce various side effects such as osteoporosis, cardiovascular effects, headaches, and vomiting. 16 Traditional herbal medicines have been widely applied for the treatment, cure, and prevention of many diseases. 17 Accumulating literature suggests that traditional herbal medicines may be recognized as a potential alternative for treating asthma, because the extracts of some medical plants (e.g., Herissantia tiubae, Aster yomena) can effectively attenuate asthma symptoms and have comparable efficacies with the commonly used asthma drugs in the modern system of medicine.…”
Section: Introductionmentioning
confidence: 99%
“…18,19 Nevertheless, there is still a lack of information on the study of the toxicological profiles and clinical tests of plant extracts. 16 Curcumol, as a bioactive sesquiterpenoid, is extracted from Rhizoma Curcumae. ( 6) 20 It has various pharmacological properties (e.g., antiviral, antifungal, antimicrobial, anticancer, and anti-inflammatory) with low cytotoxicity.…”
Section: Introductionmentioning
confidence: 99%
“…T helper cells play crucial roles in the pathophysiological process of allergic asthma. 5,6 T helper 2 cell (Th2)-mediated immune response and airway inflammation are the key characteristics of this chronic disorder. 7 Upregulation of Th2-associated cytokines, such as interleukin (IL)-4, IL-5, and IL-13, in asthmatic patients induces the infiltration and activation of eosinophils in the lung.…”
Section: Introductionmentioning
confidence: 99%